Remaking Japan : - Cohen, Theodore (Free Press, 1987)
The book reveals how that policy was hammered out and the means by which the resulting directive, JCS 1380/15, was translated into action. MacArthur and staff had to deal with the threat of nation-wide famine, economic collapse, general strikes and many other crises while imposing sweeping radical reforms that in the end set the stage for Japan's emergence as the economic giant it is today.